2016
DOI: 10.1016/j.bej.2016.01.027
|View full text |Cite
|
Sign up to set email alerts
|

A gold nanoparticle piezoelectric immunosensor using a recombinant antigen for detecting Leishmania infantum antibodies in canine serum

Abstract: Visceral leishmaniasis (VL) is a severe systemic and infectious disease potentially fatal when undiagnosed or untreated. So far, accurate diagnosis is still a problem, especially in endemic areas and in the tracking and screening of asymptomatic dogs, which are good reservoirs and main host in urban areas. Recombinant antigens based on DNA technology have provided more reliable serological diagnostics since the specificity can be achieved easier than using whole extracts. This work reports a sensitive piezeole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In the immunoassay tests is critical to block the non-specific binding since they can produce false-positive results, reducing the specificity. Glycine is the minor amino acid found; it has been widely used in immunosensors [ 43 45 ]; primarily due to the reduced molecular weight with advantaging of does not perturb the electron transfer on the sensing surface and reducing the sensitivity by steric hindering. Hence, the decrease in the anodic peak indicated the glycine present as a blocking agent (Curve V).…”
Section: Resultsmentioning
confidence: 99%
“…In the immunoassay tests is critical to block the non-specific binding since they can produce false-positive results, reducing the specificity. Glycine is the minor amino acid found; it has been widely used in immunosensors [ 43 45 ]; primarily due to the reduced molecular weight with advantaging of does not perturb the electron transfer on the sensing surface and reducing the sensitivity by steric hindering. Hence, the decrease in the anodic peak indicated the glycine present as a blocking agent (Curve V).…”
Section: Resultsmentioning
confidence: 99%
“…To reduce non-specific binding, glycine solution (10 μmol L −1 ) was added; a volume of 20 μL was placed and left incubating for 30 min, and the device was again washed and dried ( Figure 1 E). Glycine was used as an agent to prevent non-specific antibody binding on the device surface and to have a low dielectric constant [ 18 , 19 , 20 , 21 ]. In previous work, we have demonstrated that the glycine coating works directly on the ZnO nanorods since it has a good affinity for carboxylic groups [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The QCM apparatus often suffers from the influence of the surrounding noise and may lack sensitivity, especially in the case of low molecular weight analytes. Thus, recent approaches propose the application of novel NPs, nanomaterials, and nanocomposites. , For instance, highly biocompatible Au NPs providing a high surface-to-volume ratio were used by Chu et al. to improve the sensor performance .…”
Section: Transduction Mechanismsmentioning
confidence: 99%
“…Thus, recent approaches propose the application of novel NPs, nanomaterials, and nanocomposites. 481,482 For instance, highly biocompatible Au NPs providing a high surface-to-volume ratio were used by Chu et al to improve the sensor performance. 483 The surface coverage by Au NPs increased the number of the binding sites for Ab's and, subsequently, the mass of the target analyte.…”
Section: Chemical Reviewsmentioning
confidence: 99%